2023
DOI: 10.21203/rs.3.rs-2559956/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics Study of Mechanical and Tribological Behaviour of Gr/Sn Dispersed Al-7Si Alloy Matrix Composite Processed Through Bottom Pouring Stir Casting Technique

Abstract: Among numerous techniques to manufacture Aluminium metal matrix composites, the stir-casting route is employed for mass production because of less expensive. In this work, Al-7Si alloy-based composites reinforced with 10wt% graphite and x wt% of tin (x = 0, 2.5, 5, 7.5 and 10) microparticles are manufactured through the bottom pouring casting route. This study deals with the various effect of the mechanical properties, and wear resistance of Gr, and Sn particulates reinforced Al-7Si alloy matrix composite. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…According to the findings of Thoufiq and Manisekar [45], when Sn particles were excessively added, porosity increased, and wear resistance decreased. Ajay et al [48] fabricated Al-7Si/10Gr/xSn composites using a bottom pouring stir casting route. The results revealed that the inclusion of Sn with Gr in the A356 alloy matrix enhanced the wear and mechanical characteristics of the fabricated composites.…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings of Thoufiq and Manisekar [45], when Sn particles were excessively added, porosity increased, and wear resistance decreased. Ajay et al [48] fabricated Al-7Si/10Gr/xSn composites using a bottom pouring stir casting route. The results revealed that the inclusion of Sn with Gr in the A356 alloy matrix enhanced the wear and mechanical characteristics of the fabricated composites.…”
Section: Introductionmentioning
confidence: 99%